Resultados de la micropropagacion in vitro del Eucaliptus citriodora Hook - Rojas Caballero, A.=700 1 Gil Diaz, V.; Perez Bravo, C.; Darias, M.L.
(En, Es)
ilus., 4 ref.
Keywords: EUCALIPTUS CITRIODORA; MICROPROPAGACION IN VITRO; CUBA